Postmenopausal hormone replacement and venous thromboembolism following hip and knee arthroplasty - Hurbanek, Jason G.; Jaffer, Amir K.; Morra, Nariman; Karafa, Matthew; Brotman, Daniel J. (Thrombosis and Haemostasis, 2004)
Hormone replacement therapy has been associated with venous thromboembolism. Controversy exists regarding the appropriate management of hormone replacement in the perioperative setting and in other situations – such as acute illness – predisposing to acute venous thromboembolism. We performed a case-control study to determine whether perioperative hormone replacement is associated with venous thromboembolism following hip and knee arthroplasty. 108 patients with postoperative venous thrombosis were matched by age, date and type of surgery, and surgeon with 210 controls without thrombosis. Perioperative hormone replacement use was no more prevalent in patients with postoperative thrombosis than those without. Eighteen (16.7%) women with post-operative thrombosis had taken perioperative hormone replacement compared to 49 (23.3%) of controls: odds ratio = 0.66; (95% CI 0.35–1.18; p=0.17). After multivariate analysis, the adjusted odds ratios were similar. Variables predicting post-operative thrombosis included: prior venous thromboembolism (OR = 2.3; p = 0.02), rheumatologic disease (OR = 2.2; p = 0.03), and absence of pharmacologic antithrombotic prophylaxis (OR = 13.4; p = 0.005). Cases and controls were otherwise similar. Users of hormone replacement were similar to non-users except that they were less likely to have coronary disease (OR 0.34; p = 0.03) or prior thrombosis (OR = 0.28; p = 0.04), and were younger (median age 67 versus 74 years; p <0.0001). We found no association between perioperative hormone replacement and post-operative thrombosis in patients undergoing major orthopaedic surgery. Routine discontinuation of these medications preoperatively – and possibly in other situations predisposing to thrombosis, such as acute medical illness – may be unnecessary in patients receiving appropriate pharmacologic antithrombotic prophylaxis.
Keywords: Hormone replacement therapy; selective oestrogen receptor modulator; venous thromboembolism; surgery; arthroplasty